What makes people decide to pay more? Understanding cooperation in the context of an alternative food network. - Lavín, Claudio; Espejo, Alvaro; Bravo, Diego; Morales, Sebastián (Asian Journal of Social Psychology, 2015)
In recent decades, cooperative behaviour has been the target of much research. Although there is some evidence about the motives that lead people to engage in cooperation, there is still little research on cooperation models in real-life settings. To shed some light on this issue, we studied cooperation in an alternative food network. This organization is based on social and environmental concerns, and its appeals to subscribers can be operationalized as a real-life expression of cooperative behaviour. The research aimed to understand the motives behind people’s subscription to the organization and whether their motivations are consistent with traditional experimental evidence about cooperative decision-making. The results reveal that subscribers explained their participation in the organization by reporting self-oriented and other-oriented motivations and that their decision was motivated by the match between the structural characteristics provided by the organization and their individual concerns. These findings suggest that people seek to benefit both themselves and others and indicate that a conjunction between structural frames and individual ethical values is critical for explaining human cooperation.